1978
DOI: 10.1111/j.1399-6576.1978.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholinesterase Variants in the Danish Population

Abstract: A total of 1278 adult patients were screened for serum cholinesterase (E.C. 3.1.1.8) variants. The following were used for phenotyping of variants: dibucaine, fluoride, chloride, and urea. The observed incidence of cholinesterase variants in the Danish population was similar to that found in other European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Technical difficulties may also, in part, explain the considerable variations in the EJ' gene frequencies reported from different laboratories, even when otherwise genetically similar populations were tested (HANEL et al 1978). In an attempt to substantiate the EJ' gene frequency reported here, additional methods of identification were employed.…”
Section: Discussionmentioning
confidence: 87%
“…Technical difficulties may also, in part, explain the considerable variations in the EJ' gene frequencies reported from different laboratories, even when otherwise genetically similar populations were tested (HANEL et al 1978). In an attempt to substantiate the EJ' gene frequency reported here, additional methods of identification were employed.…”
Section: Discussionmentioning
confidence: 87%
“…Reid et al found that after neostigmine reversal of rocuronium-induced neuromuscular blockade when T1 was 25%, only 14 out of 40 patients attained a train-of-four ratio of 0.8 within 15 min of reversal administration. 3 The difference in drug acquisition costs according to the authors was only 2 /patient in favour of rocuronium but the difference in recovery times (six minutes) was 45 /patient in favour of mivacurium. Even if we agree on the difference the authors reported in the recovery times, mivacurium use still costs 43 less/patient.…”
Section: Short-acting Neuromuscular Blocking Drugs Allow Better Contrmentioning
confidence: 99%